KAJIAN MOTIVASI DAN DISIPLIN PEGAWAI DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG - Puspitasari, Nilam Yuniar; Sulandari, Susi; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Lack of motivation and discipline in the Dinas Kebudayaan dan Pariwisata Kota Semarang has prompted the author to undertake the study, entitled Study of Motivation and Discipline Employees at the Dinas Kebudayaan dan Pariwisata Kota Semarang.This study aims to describe and analyze the motivation and discipline in the Dinas Kebudayaan dan Pariwisata Kota Semarang. The data was collected through the distribution of questionnaires to a sample population of 64 people and a number of 32 employees in the Dinas Kebudayaan dan Pariwisata Kota Semarang. Type of research is descriptive research. The method of data analysis in this study using qualitative data analysis methods using frequency distribution table to find out the average results.The analysis showed that motivation and discipline in the Dinas Kebudayaan dan Pariwisata Kota Semarang quite good, with a summary score of 2.88 and the motivation variable summary score variable discipline of 3.09.Recommendations from this study were (i) giving compliments to employees who successfully perform the job well, (ii) in accordance with tupoksi staffing, educational background, and experience of employees, (iii) enhance the relationship between subordinates with leadership, (iv ) the need for supervision and sanctions attached to a firm such as payroll deductions for employees who arrive late, (v) conducted similar research outside variables motivation and discipline.